PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE PRACTICE REHEARSAL PAIRS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI MIA SMA MUHAMMADIYAH 1 PADANG - Nandes, Puput Putri (Pendidikan Matematika, 2014)
This research was derived from the studentsâ low understanding on mathematics concept. This was caused by the lack of interaction among the students during the teaching and learning process. This research was designed for revealing whether the use of Practice Rehearsal Pairs active learning strategy affected the studentsâ mathematics conceptual understanding. This was a pre-experimental research which used Pre-Test and Post-Test Group design. The subject of the research was the students in class XI of SMA Muhammadiyah 1 Padang. To collect the data, a pre-test and a post-test were administered. Based on the result of data analysis, it was figured that the average score of the students in the experimental class was 54,875 in the pre-test and 74,8375 in the post-test. The result of the hypothesis test showed that the value of tcalculated 7,46 was higher than ttable 2,093 indicating that the hypothesis was accepted. Thus, it was concluded that the use of Practice Rehearsal Pairs active learning strategy exerted an influence upon the studentsâ mathematics conceptual understanding on the reliability level 95%.